If only we knew what we know : the transfer of internal knowledge and best practice - O'Dell, Carla; Grayson, Jr., C. Jackson (New York : The Free Press, 1998)
Business
Includes index and bibliographical references
1999-09-01
Keywords: Knowledge; Communication; Management